From White Painting to Silent Piece: interaction between concepts and inspiration of art and music - Jianpinidnun, Apirak (Silpa Bhirasri (Journal of fine arts), 2022)
After the release of 4’ 33 or Silence Piece by John Cage in 1952, all sound in music, not only tune but also noise, has been counted significant. Like art, which is not considered a representation of reality or beauty, music composition is then not created for pleasure any more. This journal aims to reveal concept of transparency, which creates philosophical meaning in the work 4 ’33 like the silence originated in abstraction in cubism art and substantially developed in modern architecture. The concept was then adapted in music 4 ’33 by John Cage, who was inspired by Robert Rauschenberg’s White Painting (1951). The research here is done by surveying the concept and production of White Painting, interview with Cage and his explication. The analysis of Cage’s and Rauschenberg’s works revealed close relationship between music and art, which was created through absolute interaction of philosophical, religious, art and music concepts and expressions in the temporary period of the creation. The result suggests that the concept of Cage influenced by Eastern philosophy and Buddhism, such as self – deprecation and prejudice reduction, results in the process of embracing things to create one’s identity or blending oneself with things. Consequently, there is an absent of borders between beauty and crudeness, or tune and noise. Moreover, unintentional enterprise in the creativity of painting and music encourages the audiences to concern about other things beyond the music notes and elements of paintings. Most of all, they absolutely realise harmony of the antithesis, the basis of contemporary art and music, which is more essential than beautiful pictures or sound.